A Multidimensional Approach in Feminist Ecological Biblical Studies - Elvey, Anne F. (The Oxford handbook of feminist approaches to the Hebrew Bible, 2020)
In the context of anthropogenic climate change, loss of biodiversity, and the extinction of species, ecological hermeneutics has developed in two major strands: The Earth Bible Project based in Adelaide, South Australia, and The Uses of the Bible in Environmental Ethics Project, based in Exeter, UK. Neither project specifically takes up a feminist perspective, but both are, to varying degrees, in debt to feminist biblical studies. One significant area of tension is the question of the priority of the ecological over the feminist in a situation of critical ecological concern. This essay situates ecological hermeneutics in relation to feminist hermeneutics. It focuses on Genesis 1–3 and 6–9, and refers to prophetic and wisdom literature. Violence against women and Earth is the prompt for ecological feminist hermeneutics. In response to such violence, ecological feminist interpreters affirm material agency, reimagine human identity, are open to Earth’s agency in the reading process, and practice biblical interpretation as a form of partnership with Earth. Ecological feminist approaches not only engage with the multiplicity of Earth as partner in their readings but also integrate feminist, postcolonial, and other contextual approaches into a multidimensional reading praxis.